25-OH Vitamin D and Interleukin-8: Emerging Biomarkers in Cutaneous Melanoma Development and Progression. (4th October 2015) - Ene, Corina-Daniela; Anghel, Amalia-Elena; Neagu, Monica; Nicolae, Ilinca
Abstract : Background . There are several circulatory biomarkers that are involved in forecasting the clinical outcome of cutaneous melanoma. Serum/plasma vitamin D status is one of the markers intensively studied in this type of cutaneous cancer. The combination of validated serum biomarkers (like LDH) with new biomarkers such as IL-8, angiogenic factor, and vitamin D is still at the dawn of research. Hence, we are aiming to establish the predictive power of inflammatory biomarkers, such as IL-8, and metabolic ones, such as vitamin D. These candidate biomarkers are intended to aid classical biomarkers, such as LDH, in the prognosis of cutaneous melanoma. Methods. Serum vitamin D and IL-8 were quantified in melanoma patients and in matching healthy controls. Results. Median serum vitamin D concentrations were significantly lower (p = 0.003 ) in melanoma patients as compared to healthy control subjects, while around 65% of the investigated patients have proven a severe circulatory deficiency of this vitamin. IL-8 was found increased (p = 0.001 ) in melanoma patients as compared to controls. Conclusion. Upregulation of proangiogenic factors associated with vitamin D deficiency can prove to be potent future biomarkers candidates, enhancing the predictive power of classical LDH.